OPTIMALISASI PORTOFOLIO INVESTASI DANA PENSIUN UNIVERSITAS MUHAMMADIYAH MALANG - Novita Ratna Satiti (Manajemen Bisnis, 2013)
Novita Ratna SatitiProgram Studi Manajemen FEB UMME-mail: novitasuprihadi@gmail.comABSTRACTThe research aimed to optimalize investment scenario for Pension Fund of UMM. Pension Fund ofUMM optimized investment activity yet, due to the nature was still very conservative. The first phaseresearch was to evaluate the performance of investments by analyzing the value of ROI, look at thepattern of risk of each investment instrument (Standard Deviation), and calculate the average risk forfinancial assets which was invested with the VaR. The second was to develop a simulation of investmentscenario, which previously had projected prior average annual returns for various types of investments.After developing, the evaluation of simulation scenarios by analyzing the ROI and calculatedthe average risk (VaR). The results based on optimalizing investment scenarios III, by leveraging newinvestment opportunities to maximize the full potential of investments that might be made . On the thirdscenario, the ROI achieved at the value of 9.7% VaR of 0.3% in the level confidence of 99%. It means,there would be 1% chance of loss that more than 0.3%. At these scenarios, there was a change increasesthe yield of 5.4%, and was followed by increased average risk of -0.25%. On the third scenarioformation, it was expected that pension fund get scientific considerations in determining the investmentportfolio for the coming period.Keywords: Pension Funds, Investment Optimization, Scenario Portfolio Investment, Return on Investment(ROI), Value at Risk (VaR)